Improving the quality of potentiometric pH measurements - Guiomar, M. J. (2015)
Like all experimentally determined physical and chemical properties, pH measurements are affected by the limited precision and accuracy of the measurement procedures. Fundamental studies of pH standards, based on measurement of the potential of an electrochemical cell without transference, known as the Harned cell, containing a platinum-hydrogen electrode and a silver-silver chloride reference electrode, indicate that vapour condensation phenomena on potentiometric cell walls not immersed in the thermostatic bath are a major source of error in assessment of pH values. In this work a study was conducted on phthalate buffer, 0.05 mol kg(-1)supercript stop KHPhth, and results are reported for the effect of this phenomenon on the assignment of pH values and on their corresponding uncertainties. Identification and quantification of this effect constitute an original contribution to improvement of the primary method of pH measurement and, therefore, more rigorous pH (PS) values.